KINERJA UNIT PELAKSANA TEKNIS DAERAH (UPTD) JEMBATAN TIMBANG DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA PROVINSI SULAWESI UTARA ( SUATU STUDI DI UPTD JEMBATAN TIMBANG PINELENG) - MONGKAREN, BILL CLINTON; Rorong, Arie Junus; Tampi, Gustaf Budi (Sam Ratulangi University, 2016)
ABSTRACT :This study aims to identify and observe the performance of Regional Technical Implementation Unit (UPTD) Weigh Department of Communication and Information Technology of North Sulawesi province, in UPTD Weigh Pineleng in carrying out its duties and responsibilities. Based on Government Regulation No. 35 Year 2000 regarding Government Authority and Authority of the Provincial Government as Autonomous Region, the provincial government has the authority in the field of licensing and control overloading and orderly use of roads in the province, setting a maximum limit load, and to determine the location and management of Weigh Bridges. But in practice as well as the fact that there are showing problems - problems that arise, such as oversight of the leadership that is still not good, causing a lot going on extortion, then the problem of infrastructure to support the performance such as CCTV, computer administration, a printer, a patrol vehicle, then the problem of coordination and disciplinary problems.The research method used in this study is a qualitative method, the technique of primary and secondary data collection is done by library studies and field studies (interviews, documentary studies and observations). As for the informants of this study is the first person UPTD Head Weigh, 1 Head of Operations Section Weigh Wangurer and Pineleng, 4 service users (motorists), 6 Employees / Officers Operations Weigh Pineleng.The results showed that the performance Regional Technical Implementation Unit (UPTD) Weigh Department of Communication and Information Technology of North Sulawesi Province, in UPTD Weigh Pineleng measured from the concept by Gibson (1989) with the indicator, namely productivity, efficiency, Keadaptasian, Satisfaction and Development , In view of the aspect of Satisfaction, and Productivity Keadaptasian can say is not maximized. This occurs because the view-level results of work done UPTD program Weigh Pineleng still complaints from service users or motorists at Weigh Stations. Then, from the aspect of development and efficiency is still lack of training, supervision, and coordination and discipline as well as the infrastructure that still support.Referring to the discussion and conclusions above, it is suggested Leaders Weigh UPTD more firmly in control, coordination, and as well as disciplinary sanctions against employees in performing their duties and functions. Besides the need for provision of facilities and infrastructure to support the increase in UPTD Weigh administration Pineleng such as computers, printers, CCTV, patrol vehicles, and loading and unloading equipment.Keywords: Performance, UPTD Weigh